The Economy as an Order of Freedom: The Political Philosophy of the Social Market Economy. (Cultura Económica, 2025)
This article analyzes the social market economy as a political-economic model that combines individual freedom with a regulatory framework designed to guarantee social justice and general well-being. Emerging as a response to the social crisis in interwar Germany and the rise of totalitarianism, this movement, driven by the Freiburg School and figures such as Walter Eucken, other thinkers such as Wilhelm Röpke and Alfred Müller-Armack, and politicians such as Ludwig Erhard, proposes overcoming both laissez-faire and excessive state interventionism through a strong state that guarantees clear rules and limits monopolies. Ordoliberalism maintains that regulated competition is the condition for freedom to avoid self-destruction, emphasizing individual responsibility and the ethical function of the economic order. Today, this model faces challenges such as the environmental crisis, financial speculation, and surveillance capitalism, which require updating its principles to keep human dignity at its core. The social market economy thus presents itself as a viable alternative that unites the market, democracy, and ethics in an order of responsible freedom.
Keywords: Ordoliberalism; competition and freedom; subsidiarity; social justice; ethics and economics